Kitāb al-Ḥarakat al-Islāmīyah Fahm Dīnamīkīyah al-Islām al-Kharm al-Jāmi’ī Indūnīsīyā al-Mu’āṣirah - Setyadi Sulaiman; Testriono Testriono (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2008)
Research in various public institutions of higher education in Indonesia, which forms the basis of this article revealed that - especially Islamic - books have been greatly influential in the dissemination process of individual thoughts, especially among campus Islamic activists. The original thought of an individual is influenced by his/her prior experiences, In the modern context, this means, by the most important media: books. Thus, the process of the transmission of ideology among campus Islamic activists is shaped by reference works published by Islamic publishers. It is therefore safe to say that books are the means of transmission for campus Islamic movements in IndonesiaDOI: 10.15408/sdi.v15i2.533